2023
DOI: 10.3390/pr11113093
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Prediction of Deep Coalbed Methane Content in Daning-Jixian Block, Ordos Basin, China

Zheyuan Ouyang,
Haichao Wang,
Bin Sun
et al.

Abstract: The potential of deep coalbed methane resources is substantial. Gas content is an important parameter for resource assessment. At present, the gas content test method commonly used for shallow coal reservoirs is not suitable for determining deep coalbed methane gas content. Therefore, it is urgent to establish a prediction method for deep coalbed methane gas content. This study aims to quantitatively predict the gas content of coalbed methane in deep coal reservoirs and uncover its influencing factors. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…D 3 of the coal samples was less related to PV and SSA, indicating limited impact of mesopores and macropores on gas adsorption. Furthermore, the large proportion of micropores in the coal samples indicated that the adsorption properties of coal rock were primarily determined by micropores, further explaining the increase in free gas content in some deep CBM reservoirs …”
Section: Discussionmentioning
confidence: 96%
“…D 3 of the coal samples was less related to PV and SSA, indicating limited impact of mesopores and macropores on gas adsorption. Furthermore, the large proportion of micropores in the coal samples indicated that the adsorption properties of coal rock were primarily determined by micropores, further explaining the increase in free gas content in some deep CBM reservoirs …”
Section: Discussionmentioning
confidence: 96%
“…The reservoir and production characteristics of the deep CBM differ significantly from those of the middle and shallow layers. In conditions of high temperature and pressure, a portion of CBM undergoes a transition from an adsorbed state to a free state. , The deep reservoir exhibits the coexistence of adsorbed and free gas, along with conditions conducive to free gas preservation, resulting in the abundance of free gas in the deep coal reservoir . Additionally, the DJ block’s deep coal reservoir displays favorable conditions for reservoir formation, including high thermal evolution, excellent hydrocarbon generation capacity, well-developed reservoir micropores, and optimal preservation conditions .…”
Section: Introductionmentioning
confidence: 99%
“…In China, a large-scale deep coalbed methane block was built on the southern margin of Yanchuan [10]. Since 2021, several coalbed gas wells with a depth of more than 2000 m have produced tens of thousands of cubic meters of gas per day in the Junggar Basin and the eastern margin of the Ordos Basin [11][12][13]. Therefore, the study of methane adsorption characteristics in deep coal reservoirs is a hot topic, which can help predict the total exploitable methane content in deep coal reservoirs [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Coal with a high content of aromatic carbon has a strong adsorption capacity, whereas coal with aliphatic structures and oxygencontaining functional groups exhibits a weaker capability for methane adsorption [25,26]. Pressure has a positive effect, whereas temperature has a negative effect on the adsorption of methane [13]. There are various models used to describe the adsorption of methane on coal, including the Langmuir model, BET model, D-A model, and D-R model [1,3,4,27,28].…”
Section: Introductionmentioning
confidence: 99%